2003
DOI: 10.1182/blood-2002-05-1320
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin (diferuloylmethane) down-regulates the constitutive activation of nuclear factor–κB and IκBα kinase in human multiple myeloma cells, leading to suppression of proliferation and induction of apoptosis

Abstract: Because of the central role of the transcription factor nuclear factor-B (NF-B) in cell survival and proliferation in human multiple myeloma (MM), we explored the possibility of using it as a target for MM treatment by using curcumin (diferuloylmethane), an agent known to have very little or no toxicity in humans. We found that NF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
472
2
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 650 publications
(518 citation statements)
references
References 53 publications
(85 reference statements)
31
472
2
13
Order By: Relevance
“…We recently found that fresh BM cells obtained from MM patients express constitutively active NF-kB and STAT3 (Bharti et al, 2004). Furthermore, MM patients' myeloma cells constitutively produce IL-6 (CatlettFalcone et al, 1999;Bharti et al, 2003). Thus, it is possible that constitutively activated NF-kB induces the production of IL-6, which in turn activates STAT3 (Kaptein et al, 1996;Chatterjee et al, 2002) and MM cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that fresh BM cells obtained from MM patients express constitutively active NF-kB and STAT3 (Bharti et al, 2004). Furthermore, MM patients' myeloma cells constitutively produce IL-6 (CatlettFalcone et al, 1999;Bharti et al, 2003). Thus, it is possible that constitutively activated NF-kB induces the production of IL-6, which in turn activates STAT3 (Kaptein et al, 1996;Chatterjee et al, 2002) and MM cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we used U266-B1 cells, which constitutively express active NF-kB (Ni et al, 2001;Bharti et al, 2004) and produce IL-6 (Catlett-Falcone et al, 1999;Bharti et al, 2003). We incubated U266-B1 cells with Atiprimod at increasing concentrations for 4 h, and with 8 mM for 1, 4, 6, 8, and 24 h and tested the NF-kB activity in nuclear extracts.…”
Section: Atiprimod Blocks the Activation Of Nf-jbmentioning
confidence: 99%
“…The antiproliferative effects of diosgenin were also monitored by the thymidine incorporation method (Bharti et al, 2003).…”
Section: Thymidine Incorporation Assaymentioning
confidence: 99%
“…40, 41 Celastrol inhibited constitutively active NF-B in both of these cells ( Figure 4C-D). These results indicate a lack of cell-type specificity.…”
Section: Celastrol Inhibits Constitutive Nf-b Activationmentioning
confidence: 99%